„Umowy nienazwane" w grupowym systemie pracy - Zieliński, Tadeusz (Wydział Prawa i Administracji UAM, 1988)
According to the Labour Code of 1974 the employment relationship is an obligation between a single employee and an employer. The basis of such a relationship is the employment contract concluded with each employee separately. The Polish labour legislation does not provide for the institution of so-called group employment relationships concluded by several people jointly on the one hand and an employer on the other. However, such contracts appear in connection with a new trend of introducing in state enterprises so-called group forms of work organization. By virtue of such contracts, a voluntarily established group of people assumes the obligation of performing jointly a given production task for a stated remuneration which is later divided among the members of a group by the independent decision of the whole group. According to the majority opinion of legal scholars, such contracts are not a legally separate type of contracts but are in fact only a sum of so-called „autonomous clauses", i.e. contractual stipulations which complement the contents of employment contracts concluded by an employer with each individual member of a group. The author criticizes the above view and tries to prove that the basis of employing in a group system of work is a separate contract for collective labour which may be characterized as an innominate contract concluded between an employer on the one hand and a group of employees on the other. The above contract is a source of a so-called joint obligation on the part of the members of a group. The said contract is not the employment contract yet it contains elements typical for a contract of employment as well as a contract for performing a specified task or work and — with respect to relations between the members of a group — elements similar to those appearing in the partnership contract. A complex structure of those group contracts indicates that they are mixed contracts (a type of innominate contracts) imposing the obligation to achieve a stated effect and burdening the employment with a part of the risk to carry out that task. Since the employment contract components prevail, the said contracts are subject to the labour law regulation. Hence, the members of a group enjoy full protection granted by the labour law to people employed by virtue of contracts falling under the Labour Code provisions. The author postulates to adopt the provisions regulating the said type of innominate contracts in the amendments to the Labour Code. In his way a new type of a contract — a contract for rendering collective work — would appear in the Polish labour law. The author agrees in principle that it is high time to break away from a stereotype of the employment contract as a due diligence contract (locatio conducilo operarum), radically different from a contract for performing a specified task or work (locatio conductio operis). The elimination of differences between those two kinds of contracts finds justification in the world trends to make the labour law more flexible in response to the incoming „third wave" of the civilization of our epoch.
„Innominate contracts" in a group system of work